Commentary - ordering lab tests for suspected rheumatic disease - Jarvis James N (BMC, 2008)
Abstract One of the least-appreciated advances in pediatric rheumatology over the past 25 years has been the delineation of the many ways in which children with rheumatic disease differ from adults with the same illnesses. Furthermore, we are now learning that paradigms that are useful in evaluating adults with musculoskeletal complaints have limited utility in children. Nowhere is that more true than in the use of commonly used laboratory tests, particularly antinuclear antibody (ANA) and rheumatoid factor (RF) assays. This short review will provide the practitioner with the evidence base that supports a more limited use of ANA and RF testing in children.